Alzheimer Disease Biomarkers in Clinical Practice: A Blood-Based Diagnostic Revolution - Madeline M. Paczynski; Gregory S. Day (SAGE Publishing, 2022)
An estimated 6.1 million Americans live with cognitive impairment-a number that is expected to triple by 2050. Alzheimer disease (AD) is the most common cause of impairment. The development of blood-based biomarkers capable of detecting pathological changes of AD in living patients has the potential to revolutionize the diagnostic approach to cognitive impairment by enabling screening for AD using accessible, non-invasive measures of amyloid and tau neuropathology, with accuracy that increasingly approaches that seen with "gold standard" positron emission tomography and cerebrospinal fluid measures. Demand for biomarker testing is expected to intensify with the emergence of effective treatments for AD and related dementias. Clinicians in all fields must prepare to meet this demand. Primary care practitioners are well positioned to support dementia diagnosis and management, including the application and interpretation of biomarkers. This article reviews the current uses of AD biomarkers and the potential applications of emerging blood-based AD biomarkers in clinical practice.